PENGARUH MANAJEMAN SUMBER DAYA MANUSIA TERHADAP MUTU PENDIDIKAN DI SDN 1 CIBUNIGEULIS KOTA TASIKMALAYA - Malik, Amarullah; Siska Nurlia (Manajerial | Journal Manajemen pendidikan islam, 2025)
Education serves as the main foundation for developing high-quality and competitive human resources. The quality of education is significantly influenced by how effectively educational institutions manage their human resources. At the elementary school level, optimal management of teaching and administrative staff is a key factor in ensuring successful learning outcomes. SDN 1 Cibunigeulis was selected as the research site due to its active progress in human resource management and its strong commitment to improving educational quality. This study aims to analyze the effect of human resource management on the quality of education at SDN 1 Cibunigeulis, Tasikmalaya. A quantitative approach with an ex post facto design was employed. The population consisted of 20 teaching staff, all of whom were included in the sample using total sampling technique. Data were collected through validated and reliable questionnaires and analyzed using simple linear regression. The results shows that the implementation of human resource management and the quality of education are in the moderate category, with average scores of 52.65 and 50.65, respectively. Normality and linearity tests showe that the data are normally distributed and linearly related. The t-test showes a significant effect th = 2.368 > tt = 2.100; p = 0.029, supported by the Ftest Fh = 5.605 > Ft = 4.41. The coefficient of determination (R²) of 0.237, indicates that human resource management contributed 23.7% to the variance of education quality. These findings highlight the importance of effective human resource management in improving the quality of primary education.